Near infrared window active magnetic core spiky gold nanostars for dual mode imaging and photothermal therapy - Jiamin Xu; Koen Evers; Yu-chien Lin; Taveer A. Tabish; Qiyu Zhang; Ren-Jei Chung; Mary P. Ryan; Fang Xie (Materials Today Advances)
A single nanoparticle (NP) capable of simultaneously performing multiple bioimaging and therapeutic functions is an innovative approach to advance the field of cancer diagnostics and treatment. Here we report a facile synthesis approach to produce magnetic-plasmonic core-shell nanostars. These NPs consist of an Fe3O4 core, silica intermediate shell, and outer spiky gold nanostar shell. Remarkably, these core-shell NPs exhibit outstanding magnetisation and tuneable localized surface plasmon resonance (LSPR) spanning from visible to Near Infrared (NIR) wavelengths. Through incorporation of Indocyanine Green (ICG) and subsequent coating with bovine serum albumin (BSA), the obtained NPs demonstrate dual imaging capabilities in the form of magnetic resonance imaging (MRI) which offers high spatial resolution and deep tissue penetration and Surface-Enhanced Raman Scattering (SERS) which can provide the ultrasensitive molecular detection which MRI lacks. More significantly, they also exhibit significant potential to be used in photothermal therapy (PTT). These multi-functional NPs show minimal cytotoxicity when exposed to cells even at high concentrations, positioning them as promising candidates for future in vivo studies centred around imaging-guided photothermal therapy.